Literasi Keuangan pada Kelompok Wanita Telang di Desa Bandengan Kab. Pekalongan - Zahro, Zahro; Ayuningrum, Anggrainy Putri; Affan, Muhammad (Society : Jurnal Pengabdian Masyarakat, 2023)
The butterfly pea (Clitoria ternatea) are by most the community considered only ordinary plants actually have extraordinary benefit (Imayanti et al., 2019). Bandengan Village in Pekalongan Regency is one of the villages that has experienced floods since the last 10 years. Thus,  many residents especially women, have used many pots to cultivate butterfly pea plants. Moreover, women in Bandengan Village, Pekalongan Regency try to be independent in terms of income and also want to increase their capability. Womenpreneur makes a big contribution to Small Medium Enterprise in Indonesia. According to Biro Pusat Statistik  in 2021, the majority of the total  Small Medium Enterprise  in Indonesia, to be precise, 64.5 or 37 million  Small Medium Enterprise  are managed by women (BPS, 2021). The contribution of  Small Medium Enterprise  to employment is about 97% of the total workforce and able to increase about 60.4% of the total investment. However, the high number of   Small Medium Enterprise  have main problems such as low level of access to financial literation.  Small Medium Enterprise  can’t managed business and personal finance. They are have  no record of income, costs and sales. As a result, they can not identify the financial needs of their business. Hence, financial literacy training and assistance is expected to be able to increase the financial capacity of  Small Medium Enterprise owners, an make simple reports in managing their business.